Glycemic control in children and teenagers with type 1 diabetes around lockdown for COVID‐19: A continuous glucose monitoring‐based observational study. Issue 9 (2nd March 2021) - Wu, Xiumei; Luo, Sihui; Zheng, Xueying; Ding, Yu; Wang, Siqi; Ling, Ping; Yue, Tong; Xu, Wen; Yan, Jinhua; Weng, Jianping
Abstract: Aims/Introduction: The coronavirus disease 2019 (COVID‐19) pandemic urged authorities to impose rigorous quarantines and brought considerable changes to people's lifestyles. The impact of these changes on glycemic control has remained unclear, especially the long‐term effect. We aimed to investigate the impact of COVID‐19 lockdown on glycemic control in children and adolescents with type 1 diabetes. Materials and Methods: This observational study enrolled children with type 1 diabetes using continuous glucose monitoring. Continuous glucose monitoring data were extracted from the cloud‐based platform before, during and after lockdown. Demographics and lifestyle change‐related information were collected from the database or questionnaires. We compared these data before, during and after lockdown. Results: A total of 43 children with type 1 diabetes were recruited (20 girls; mean age 7.45 years; median diabetes duration 1.05 years). We collected 41, 784 h of continuous glucose monitoring data. Although time in range (3.9–10.0 mmol/L) was similar before, during and after lockdown, the median time below range <3.9 mmol/L decreased from 3.70% (interquartile range [IQR] 2.25–9.53%) before lockdown to 2.91% (IQR 1.43–5.95%) during lockdown, but reversed to 4.95% (IQR 2.11–9.42%) after lockdown ( P  = 0.004). Time below range <3.0 mmol/L was 0.59% (IQR 0.14–2.21%), 0.38% (IQR 0.05–1.35%) and 0.82% (IQR 0.22–1.69%), respectively ( P  = 0.008). The amelioration of hypoglycemia during lockdown was more prominent among those who had less time spent <3.9 mmol/L at baseline. During lockdown, individuals reduced their physical activity, received longer sleep duration and spent more time on diabetes management. In addition, they attended outpatient clinics less and turned to telemedicine more frequently. Conclusion: Glycemic control did not deteriorate in children and teenagers with type 1 diabetes around the COVID‐19 pandemic. Hypoglycemia declined during lockdown, but reversed after lockdown, and the changes related to lifestyle might not provide a long‐term effect. Abstract : Glycemic control did not deteriorate in type 1 diabetes patients around the COVID‐19 pandemics. There was a small, but significant, improvement in hypoglycemia in people with type 1 diabetes during lockdown for COVID‐19, but such improvement disappeared after lockdown. A stable and relaxed lifestyle might lead to better glycemic control, but lifestyle changes might not provide a long‐term effect.